2013
DOI: 10.17221/537/2013-pse
|View full text |Cite
|
Sign up to set email alerts
|

The effect of organic fertilizers on the biochemical properties of soil contaminated with zinc

Abstract: This study evaluates the effectiveness of organic fertilizers in restoring the homeostasis of soils contaminated with zinc. The activity of selected enzymes participating in the transformation of carbon, nitrogen, phosphorus and sulfur and the sensitivity of white mustard plants to zinc were analyzed. A greenhouse pot experiment was carried out. Uncontaminated soil served as control. Six organic substances which potentially neutralize the adverse effects of zinc were used: tree bark, finely ground barley straw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 17 publications
0
21
0
Order By: Relevance
“…At the same time, the effect is more pronounced in sandy formations than in loamy formations [36]. One may suppose that as a consequence of the significant dependence between the activity of arylsulfatase and its resistance, the addition of organic substances (i.e., cellulose, compost, manure, or bark) to soil contaminated with heavy metals may contribute to an improvement of both parameters [42].…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…At the same time, the effect is more pronounced in sandy formations than in loamy formations [36]. One may suppose that as a consequence of the significant dependence between the activity of arylsulfatase and its resistance, the addition of organic substances (i.e., cellulose, compost, manure, or bark) to soil contaminated with heavy metals may contribute to an improvement of both parameters [42].…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Wyszkowska et al (2013a) are of the opinion that straw generates much higher resistance of individual enzymes. It cannot be disputed that the stimulating effects of classic fertilizing agents were demonstrated by analyzing the tested soil samples with the EF coefficient.…”
Section: Resultsmentioning
confidence: 99%
“…The factor which may explain it is the soil's organic matter (bAdorA 2011). In soils with a higher organic matter content, a weaker toxic effect of zinc on the biochemical properties of soil is observed (bååtH 1989, Moreno et al 2009, bAdorA 2011, boros et al 2011, WyszkoWskA et al 2013a). However, studies on the activity of acid and alkaline phosphatases, enzymes involved in the cycling of phosphorus, have demonstrated that they can be inhibited by soil pollution with zinc (cAstAldi et al 2004, HinojosA et al 2004, Moreno et al 2009, kAbAtA-PendiAs 2010.…”
Section: Biological Activity Of Soils Subjected To Zinc Impactmentioning
confidence: 99%